The Influence of Financial Literacy and Reference Group toward Consumptive Behavior Across Senior High School Students - Ridhayani, Fikriyyah; Johan, Irni Rahmayani (Journal of Consumer Sciences, 2020)
Consumptive behavior is the tendency to buy goods or services without rational consideration. This study aims to analyze the influence of financial literacy and reference groups toward consumptive behavior across senior high school students. The study used a cross-sectional design and the research location was selected purposively based on the distance of the school from the shopping center area. Using the self-administered questionnaire, the study involved 125 students of public high school (SMAN) at Bogor City, that is SMAN 3 and SMAN 9. The data were analyzed using descriptive analysis and inferential statistics. The study showed that the level of financial literacy was in the medium category, while the reference group and the level of consumptive behavior were in a low category. Moreover, results indicated a relationship between the characteristics of adolescents, financial literacy, reference groups, and consumptive behavior. The regression test found a significant negative effect of financial behavior toward consumptive behavior. Females were more likely to be more consumptive, while reference groups positively influenced the consumptive behavior of senior high school students.